Combining Ability and Heterosis for Endosperm Carotenoids and Agronomic Traits in Tropical Maize Lines - Azmach, Girum; Gedil, Melaku; Spillane, Charles; Menkir, Abebe (Frontiers in Plant Science, 2021)
Provitamin A enrichment of staple crops through biofortification breeding is a powerful approach to mitigate the public health problem of vitamin A deficiency in developing countries. Twenty-four genetically diverse yellow and orange endosperm maize inbred lines with differing levels of provitamin A content were used for analysis of their combining ability. Each inbred line was developed from crosses and backcrosses between temperate and tropical germplasm. The inbred lines were grouped into different sets according to their provitamin A levels and were then inter-crossed in a factorial mating scheme to generate 80 different single-cross hybrids. The hybrids were evaluated in field trials across a range of agroecological zones in Nigeria. The effect of hybrids was significant on all the measured provitamin A and non-provitamin A carotenoids and agronomic traits. While the effect of genotype by environment (GxE) interaction was significant for almost all traits, it was a non-crossover type interaction for carotenoid content. Partitioning of the variances associated with the carotenoid and agronomic traits into their respective components revealed the presence of significant positive and negative estimates of General Combining Ability (GCA) and Specific Combining Ability (SCA) effects for both carotenoid content and agronomic traits. The preponderance of GCA effects indicates the importance of additive gene effects in the inheritance of carotenoid content. We found F1 hybrids displaying high parent heterosis for both provitamin A content and agronomic performance. Our study demonstrates that provitamin A biofortification can be effectively implemented in maize breeding programs without adverse effects on important agronomic traits, including grain yield.